Memanfaatkan Peran Umpan Balik pada Kelas Online Matematika di Era Kenormalan Baru - Varetha Lisarani (Universitas Islam Jember, 2022)
In this era of The New Normal where students, teachers, and even parents are ‘forced’ to get accustomed to distance learning, we cannot simply overlook the importance of feedback on students’ work especially in mathematics teaching and learning, since feedback will provide information about the level of students' understanding of the material provided and also encourage them because their work is valued. This is a descriptive qualitative article about the overview of online mathematics classes and also how to utilize the role of feedback in them. The data in this article was enriched with the results of a questionnaire for 83 respondents from higher education in West Borneo. The results of the questionnaire revealed that 64.5% of respondents thought that online discussion groups were the most convenient platform to use in online learning, while video conference (90,3%) recorded the least. Regarding feedback, 53.8% of respondents chose corrective information on the work of the learner as the preferred form of feedback compared to the other two. At the end of this article, also suggested some ways for teachers to provide feedbacks based on the distance learning platform used in The New Normal Era. Keywords: feedback, online class, new normal era